Switching portal technique in anterior cruciate ligament reconstruction: use of an extra low and medial portal - Agarwal, Abhishek; Debuka, Ekansh; Kumar, Dharmendra; Sharma, Vineet (International Journal of Research in Orthopaedics, 2019)
Background: Long term success of ACL reconstruction depends on accurate surgical technique of anatomic tunnel placements and proper rehabilitation protocol followed, and for accurate tunnel positioning various arthroscopic landmark should be visible clear with the use of various portals. Methods: All 112 surgeries were performed by a single surgeon in King Georges Medical University, Lucknow Orthopedic department operation theatre during July 2016- December 2018. An extra low and medial portal is created and then portal were switched between anteromedial and low medial one. Results: With the use of this portal the average surgical time was observed to be 43 minutes and no malpositioning of tunnel was encountered. Conclusions: This switching portal technique provides an excellent view of the femoral tunnel plot and gives consistent results with minimum complications.